Biracial Families Crossing Boundaries, Blending Cultures, and Challenging Racial Ideologies - Nazarinia Roy, Roudi; Rollins, Alethea (Springer International Publishing : Imprint: Springer, 2019)
This interdisciplinary volume surveys the diverse experiences of biracial families, both across and outside the black/white binary. The book examines the deep-rooted social contexts that inform the lifespan of interracial families, from dating and marriage through the stages of parenthood, as well as families' unique responses and realities. Through a variety of structures and settings including blended and adoptive families, contributors describe families' strengths and resilience in meeting multiple personal and larger social challenges. The intricacies of parenting and family development are also revealed as an ongoing learning process as parents and children construct identity, culture, and meaning. Among the topics covered: Social constitutionality of race in America: some meanings for biracial/multiracial families. Interracial marriages: historical and contemporary trends. Racial socialization: a developmental perspective. Biracial families formed through adoption. Diverse family structures within biracial families. Racial identity: choices, context, and consequences. Addressing lingering gaps in the existing literature and highlighting areas for future study, Biracial Families gives readers a fuller understanding of a growing and diversifying population. Its depth and breadth of coverage makes the book an invaluable reference not only for practitioners and researchers, but also for educators and interracial families across the spectrum.